Analyzing Semantic Properties of OCL Operations by Uncovering Interoperational Relationships - Kuhlmann, Mirco; Gogolla, Martin (Electronic Communications of the EASST, 2007)
The OCL (Object Constraint Language) as part of the UML (Unified Modeling Language) is a rich language with different collection kinds (sets, multi-sets, sequences) and a large variety of operations defined thereon. Without negating the strong correlation between both fields we can say that these operations have their origin partly in logic (like the operations forAll and exists) and partly in computer science, in particular database systems (like the operation select). Some of these operations may be expressed in terms of other operations. This paper presents a systematic study of relationships which hold between OCL features like the mentioned operations. Apart from presenting the relationships between operations in a conceptual way, the relationships are described by a formal metamodel allowing systematic and computer supported access to the operation relationships by querying an underlying formal description.